Pengaruh Jenis Umpan terhadap Hasil Tangkapan Rajungan (Portunus pelagicus) dengan Alat Tangkap Bubu di Pantai Pasir Putih Karawang - Alamika Ludirosari; Yusrudin Yusrudin; Sumaryam Sumaryam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Fishing activities of crab (Portunus pelagicus) on the white sand beach are mostly carried out by traditional fishermen using various equipment. Bubu is the recommended fishing gear for catching crab. This fishing gear is a trap and is passive and is classified as a trap type of fishing gear. One of the determining factors that increases the catch of crab (Portunus pelagicus) is bait. This study aims to determine the effect of using different types of bait and determine the most effective choice of bait in catching crabs that live on the White Sand Beach, Karawang. The method used in this study is the Experimental Method with a Randomized Block Design (RAK). The types of bait used are petek fish, puffer fish and chicken liver. Data analysis used the One-way ANOVA test and continued with the BNT Test. The number of catches obtained during the study was 66 crab (Portunus pelagicus) consisting of salted petek bait (28), salted puffer fish bait (23) and chicken liver bait (15). Based on the analysis of the results of the One-way ANOVA test, a significant value for the type of bait was obtained of 0.000 with a significant value <0.05, so it can be concluded that different types of bait have an effect on the catch of crab (Portunus pelagicus).